Effects of manipulated herbivore inputs on nutrient flux and decomposition in a tropical rainforest in Puerto Rico - Schowalter, TD; Fonte, Steven J.; Geaghan, J; Wang, J. (Springer, 2011)
Forest canopy herbivores are known to increase rates of nutrient fluxes to the forest floor in a number of temperate and boreal forests, but few studies have measured effects of herbivore-enhanced nutrient fluxes in tropical forests. We simulated herbivore-induced fluxes in a tropical rainforest in Puerto Rico by augmenting greenfall (fresh foliage fragments), frassfall (insect feces), and throughfall (precipitation enriched with foliar leachates) in replicated experimental plots on the forest floor. Background rates of greenfall and frassfall were measured monthly using litterfall collectors and augmented by adding 10× greenfall or 10× frassfall to designated plots. Throughfall fluxes of NH4, NO3 and PO4 (but not water) were doubled in treatment plots, based on published rates of fluxes of these nutrients in throughfall. Control plots received only background flux rates for these compounds but the same minimum amount of distilled water. We evaluated treatment effects as changes in flux rates for NO3, NH4 and PO4, measured as decomposition rate of leaf litter in litterbags and as adsorption in ion-exchange resin bags at the litter–soil interface. Frass addition significantly increased NO3 and NH4 fluxes, and frass and throughfall additions significantly reduced decay rate, compared to controls. Reduced decay rate suggests that nitrogen flux was sufficient to inhibit microbial decomposition activity. Our treatments represented fluxes expected from low–moderate herbivore outbreaks and demonstrated that herbivores, at these outbreak levels, increase ecosystem-level N and P fluxes by >30% in this tropical rainforest.